Analisys of teaching elements on technical and mathematical disciplines in modern distance education - Biziuk, A.; Biziuk, V.; Shakurova, T. (Technology Audit and Production Reserves, 2021)
The object of research is the quality of teaching technical and mathematical disciplines in modern distance education. One of the most problematic areas is communication, dialogue between a teacher and a student, per-sonality problems in the teacher-student dyad, and the effectiveness of feedback. The idea of distance learning, obviously, is that the interaction between teacher and student takes place in a virtual space. The more efficiently this interaction is built by using a variety of techniques, methods, the better a teaching process. Distance teaching is essentially a person-centered form of education. This is a separate modern educational technology that provides a choice for the teacher, the ability to select educational material depending on the information needs of students. In the course of the study, the main possibilities for improving the effectiveness of feedback between the student and the teacher and the forms of implementing such communication were considered. The organizational and pedagogical conditions for the use of the system of certain elements of distance learning in the process of vocational training have been substantiated. Modern information technologies and innovative teaching methods in training specialists are described. It is proposed to use more actively such elements as an interactive whiteboard, interactive processing of students’ statements during a survey, both in the form of tests or a forum, and in the form of a «word cloud». The use of these interactive elements has proven itself in practice. As a tool for objective assessment of the level of feedback, a comparative analysis of statistical data is pro-posed, which concerns the distribution of marks at the beginning and at the end of the distance learning course. This data can also be interpreted as an indicator of the quality of teaching. In particular, the analysis of school preparation of students for mastering mathematical disciplines in higher education was carried out. Comparative analysis substantiated, in particular, the need for additional classes for students with poor preparation.
Keywords: distance education; mathematical disciplines; teaching quality; feedback